Race-Specific and Skin of Color Dermatoscopic Characteristics of Skin Cancer: A Literature Review - Emmanouil Karampinis; Aimilios Lallas; Elizabeth Lazaridou; Enzo Errichetti; Zoe Apalla (Mattioli1885, 2023)
Introduction: Individuals with melanin-rich skin account for the majority of the world's population. However, literature data regarding dermoscopic characteristics of skin cancer in skin of color (SoC) are scarce. The dermoscopic characteristics of cutaneous tumors might differ among skin types due to heterogeneity in composition and pigmentation. Objectives: To summarize literature data on the dermoscopic findings of skin neoplasms according to the skin color and race. Methods:  The literature search was performed using the PubMed database up to December 30, 2022, and was conducted with the use of terms referring to dermoscopy, race (Caucasians, Hispanics, Asians, and Black/African), and skin cancer types (basal cell carcinoma [BCC], squamous cell carcinoma [SCC], keratoacanthoma, Bowen disease, and melanoma). Results: In total, 30 race-specific records were included. Nine SoC records for BCCs (2 BCC studies in Hispanics, 1 BCC study in Black individuals, and 6 BCC studies in Asians), 9 SoC records for SCCs ( 1 SCC study in Hispanics ,1 SCC study in Black individuals and 7 SCCs in Asian population), and 8 SoC records for melanoma (2 melanoma studies in Hispanics, 1  in Blacks, and 5  in Asians) were compared with 4 records that involved only a Caucasian population, according to their participant section as well as with studies on dermoscopy characteristics without focusing on race origins and phototype of the patient. Conclusion: Based on a review of studies including Caucasians, Hispanics, Asians and Blacks /Africans, SoC patients present with more frequent and unique dermatoscopy features of skin cancers.